(untitled) (Rivista di Psicopatologia Forense, Medicina Legale, Criminologia, 2021)
The following study draws its analysis in the aftermath of opening a social fan page concerning a c recent criminal case where a married couple - Laura Perselli and Peter Neumair - was murdered by their son named Benno Neumair. After analysing the alleged Facebook fan page which supported and praised the young 31 years old confessed son, a necessity was outlined whether a scientific-technical term already existed that could define individuals" - especially women - tendency to be attracted towards violent criminals. Therefore, after addressing several peer-reviewed studies and in-depth analyses, a conclusive rationale has been outlined that an indicative term that addresses what has been above-mentioned exists, and it has been defined as Hybristophilia. Furthermore, the following dissertation herein proposed seeks to provide some answers to questions likewise the ones that follow: “Why are certain people so fascinated by these vicious criminals?"; "Is the following a phenomenon that applies only to the female gender or in good percentages even to their male counterparts?"; "How much influence do these criminals have on social media or the web?".